Impact of serous macular detachment on visual recovery in retinal vein occlusion treatment - Firat,Ilknur Tuncer (2022)
ABSTRACT Purpose: The aim of this study was to evaluate the effect of serous macular detachment observed during retinal vein occlusion on treatment results. Methods: A total of 117 eyes from 115 patients who had been treated with intravitreal injections for macular edema secondary to retinal vein occlusion were retrospectively reviewed. Visual acuity, optical coherence tomography, and fundus fluorescein angiography findings were evaluated according to the status of serous macular detachment. Results: In the branch retinal vein occlusion group, a statistically significant increase was detected in the mean visual acuity compared to the baseline value at each visit in the absence of serous macular detachment, whereas the increase in the mean visual acuity was significant only at the 3- and 6-month visits in the presence of serous macular detachment. In the central retinal vein occlusion group, there was an increase in the mean visual acuity compared to the baseline value at every visit in the absence of serous macular detachment, whereas the mean visual acuity decreased compared to the baseline value at every visit except at the 3-month visit in the presence of serous macular detachment. The ellipsoid zone defect was more prominent in the presence of serous macular detachment in eyes with branch retinal vein occlusion, whereas there was no significant difference in the ellipsoid zone in the absence or presence of serous macular detachment in eyes with central retinal vein occlusion. Conclusions: In the group with macular edema due to retinal vein occlusion, the initial mean visual acuity increase observed in the first year was maintained in cases without serous macular detachment but not in those with serous macular detachment. Serous macular detachment could be a negative factor in eyes with retinal vein occlusion.